Respon Petani Terhadap Penambahan Tepung Maggot Black Soldier Fly (Hermetia Illucens) Dalam Ransum Terhadap Kualitas Interior Telur Ayam Ras Petelur - M, Mihrani; Ardana, A.T.P. (Yayasan Daarul Huda Kruengmane, 2025)
This study aims to determine the administration Farmers' response to the provision of black soldier fly maggot flour (Hermetia illucens) in rations on the interior quality of laying hen eggs. The outreach was conducted in TA Village, Tanete Riattang District, Bone Regency, in June 2023. Extension evaluation was performed at the beginning and end of the study. The results indicated that a significant substitution of BSF maggot meal has an impact on the observed parameters. Substituting concentrate with up to 15% BSF maggot meal in the diet leads to improved egg internal quality, particularly in egg yolk index and egg yolk color. Furthermore, the extension evaluation showed an increase in the knowledge, attitude, and skills of respondents by 38.2%, 21%, and 38.8%, respectively. In addition, the extension program meets the criteria for being considered effective.